2022
DOI: 10.1111/jdv.18594
|View full text |Cite
|
Sign up to set email alerts
|

Real‐life effectiveness of tildrakizumab in chronic plaque psoriasis: A 52‐week multicentre retrospective study—IL PSO (Italian landscape psoriasis)

Abstract: Background: Tildrakizumab is a humanized monoclonal antibody that binds selectively the p19 subunit of interleukin-23. It is approved for treatment of moderatesevere chronic plaque psoriasis.Objectives: We conducted a 52-week retrospective study to assess the effectiveness and safety of tildrakizumab in a real-life setting.Methods: Our retrospective study included 237 consecutive adults with moderateto-severe plaque psoriasis, enrolled in 10 different Italian centres, treated with tildrakizumab up to Week 52. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
24
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 39 publications
(100 reference statements)
6
24
2
Order By: Relevance
“…40 A recently published retrospective, multicenter real-life study, enrolled a total of 237 patients treated with tildrakizumab up to 52 weeks. 41 Authors' results were in line with our study, showing comparable rates of both PASI 90 and PASI 100 at week 52, which were reached by 73.55% and 58.68% of patients, respectively. 41 An interesting data regarded the difference between bio-naïve patients, in which the efficacy of tildrakizumab resulted to be significantly higher than bio-experienced patients.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…40 A recently published retrospective, multicenter real-life study, enrolled a total of 237 patients treated with tildrakizumab up to 52 weeks. 41 Authors' results were in line with our study, showing comparable rates of both PASI 90 and PASI 100 at week 52, which were reached by 73.55% and 58.68% of patients, respectively. 41 An interesting data regarded the difference between bio-naïve patients, in which the efficacy of tildrakizumab resulted to be significantly higher than bio-experienced patients.…”
supporting
confidence: 91%
“…41 Authors' results were in line with our study, showing comparable rates of both PASI 90 and PASI 100 at week 52, which were reached by 73.55% and 58.68% of patients, respectively. 41 An interesting data regarded the difference between bio-naïve patients, in which the efficacy of tildrakizumab resulted to be significantly higher than bio-experienced patients. 41 Indeed, although our study found a slightly higher improvement in bionaïve patients, this resulted a not statistically significant difference; this may come from the higher number of patients enrolled in this study (n=237 vs n=42).…”
supporting
confidence: 91%
See 3 more Smart Citations